Pelatihan Cooperate Learning Melalui Media English Exploratory Vacation pada Mahasiswa Sadar Wisata Palembang Darussalam - Ariya Agustin; M Bambang Purwanto (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
Tourism is the entry gate to revive the economy after the pandemic ends. Many tourists treat longing that has long been constrained by the situation brought about by covid 19. In increasing the confidence of tourists visiting Palembang City, students who are members of the Palembang Darussalam Tourism forum hold English proficiency training with a cooperative learning method that aims to further increase confidence when speaking English. This is in line with the large number of foreign tourists who enter Palembang City to travel or do business. This community service activity is focused on improving the English language skills of students who are members of the Palembang Darussalam tourism aware student forum. This activity was carried out via zoom meeting by providing information about tourism in Palembang City and directly practicing speaking English.